Leadership styles of millennial entrepreneurs of small companies in the textile sector In Metropolitan Lima - Jauregui Arroyo, Ralphi (2021)
The study of leadership styles is increasingly important because it has an influence on organizational performance. In addition, their study regardingthe Millennial generation is relevant because their numbersare currently occupying managerial positions and are attributed a unique way of leading, compared to previous generations. That is why this paper aims at identifying the leadership styles of Millennial entrepreneurs of small companies in the textile sector in Metropolitan Lima. The methodology employed is quantitative and the research method is descriptive. For this end, the sample employed is of 160 entrepreneurs of small companies in the textile sector located in different districts of Metropolitan Lima, to which the Multifactor Leadership Questionnaire (MLQ) is applied. We show that Millennial entrepreneurs have a greater presence of transformational leadership, followed by transactional and passive types of leadership.